Anti-herpes simplex virus activities and mechanisms of marine derived compounds - Hao, Cui; Xu, Zhongqiu; Xu, Can; Yao, Ruyong (Frontiers in Cellular and Infection Microbiology, 2024)
Herpes simplex virus (HSV) is the most widely prevalent herpes virus worldwide, and the herpetic encephalitis and genital herpes caused by HSV infection have caused serious harm to human health all over the world. Although many anti-HSV drugs such as nucleoside analogues have been ap-proved for clinical use during the past few decades, important issues, such as drug resistance, toxicity, and high cost of drugs, remain unresolved. Recently, the studies on the anti-HSV activities of marine natural products, such as marine polysaccharides, marine peptides and microbial secondary metabolites are attracting more and more attention all over the world. This review discusses the recent progress in research on the anti-HSV activities of these natural compounds obtained from marine organisms, relating to their structural features and the structure-activity relationships. In addition, the recent findings on the different anti-HSV mechanisms and molecular targets of marine compounds and their potential for therapeutic application will also be summarized in detail.